Evaluation of trauma scoring and endothelial glycocalyx injury in cats with head trauma - Parlak, Kurtulus (Slovenian veterinary research, 2022)
This study aim to evaluate the modified Glasgow Coma Scale (mGCS) and Animal Trauma Triage (ATT) scores, labo- ratory variables, and prognostic features of trauma-induced endothelial glycocalyx injury in cats with head trauma. Twenty-five cats with head trauma and 10 healthy cats were evaluated in this study. The enzyme-linked immunosorbent assay (ELISA) method was used to measure the levels of syndecan-1 and thrombomodulin in the serum of the 25 cats with head trauma (within 48 hours) and the 10 healthy cats. In addition, mGCS scores, ATT scores, laboratory values, syndecan-1 and thrombomodulin levels were compared between the cats that survived following treatment and the cats that did not survive despite treatment. Syndecan-1 and thrombomodulin levels were not statistically different between healthy cats and cats with head trauma. In the cats with head trauma, the mGCS scoring system was found to be more sensitive than the ATT scoring system. In conclusion, syndecan-1 and thrombomodulin levels did not yield statistically significant results in the cats with head trauma.
Keywords: Craniocerebral Trauma; Glasgow Coma Scale; Glycocalyx; veterinary; Wounds and Injuries